Optimization of Nanogel Formulation of Piper Nigrum And Erythrina Subumbrans Extract As Anti-Inflammatory Based On Lontar Usadha Tiwang: Effectiveness Test On Mus Musculus - I Gede Agus Sindhu Aditama; Putu Ayu Ratih Listiani (International Journal of Health and Pharmaceutical (IJHP), 2025)
Public health in Bali has long been supported by traditional medicine based on local wisdom, one of which is usadha tiwang. In practice, usadha tiwang uses black pepper (Piper nigrum) and dadap leaves (Erythrina subumbrans) to treat mokan disease, which is characterized by swelling and pain, typical symptoms of inflammation. Scientifically, both have been proven to have anti-inflammatory activity in both extract and cream preparations, although their use in topical nanogel formulations has not been explored. This study aims to conduct phytochemical screening, develop a combination nanogel formulation of P. nigrum and E. subumbrans extracts, and evaluate anti-inflammatory activity in vivo. Extraction was performed by maceration, using 96% ethanol (1:5) for P. nigrum and 70% ethanol (1:5) for E. subumbrans. A total of six nanogel formulas were prepared with varying gel base concentrations. Activity testing was performed on mice (Mus musculus) with 1% carrageenan induction on the paw, divided into eight groups (F1–F6, negative control, and positive control). Edema evaluation was performed using a plethysmometer, and the data were analyzed using the Kruskal-Wallis test. Screening results showed that P. nigrum ethanol extract contained alkaloids, flavonoids, and steroids, while E. subumbrans extract contained alkaloids, flavonoids, saponins, and steroids. All formulations had transmittance values ​​>90%. Statistical analysis showed a significant difference between treatment groups (p=0.002). The positive control (Voltaren® Emulgel) differed significantly from all test groups (p=0.000). Of the six formulas, F3 showed the most optimal effect with an inflammation inhibition percentage of 100% at the 60th minute of observation.